Intranasal delivery of nanoliposomal SN-38 for treatment of diffuse midline glioma - Sasaki, Takahiro; Watanabe, Jun; He, Xingyao; Katagi, Hiroaki; Suri, Amreena; Ishi, Yukitomo; Abe, Kouki; Natsumeda, Manabu; Frey, William H; Zhang, Peng; Hashizume, Rintaro (Journal of neurosurgery, 2023)
Diffuse midline gliomas, including diffuse intrinsic pontine gliomas (DIPGs), are among the most malignant and devastating childhood brain cancers. Despite aggressive treatment, nearly all children with these tumors succumb to their disease within 2 years of diagnosis. Due to the anatomical location of the tumors within the pons, surgery is not a treatment option, and distribution of most systematically administered drugs is limited by the blood-brain barrier (BBB). New drug delivery systems that bypass the BBB are desperately needed to improve outcomes of DIPG patients. Intranasal delivery (IND) is a practical and noninvasive drug delivery system that bypasses the BBB and delivers the drugs to the brain through the olfactory and trigeminal neural pathways. In this study, the authors evaluated the efficacy of nanoliposomal (LS) irinotecan (CPT-11) and an active metabolite of CPT-11, 7-ethyl-10-hydroxycamptothecin (SN-38), using IND in DIPG patient-derived xenograft models. In vitro responses to LS-CPT-11 and LS-SN-38 in DIPG cells were evaluated with cell viability, colony formation, and apoptosis assays. The cellular uptakes of rhodamine-PE (Rhod)-labeled LS-CPT-11 and LS-SN-38 were analyzed with fluorescence microscopy. Mice bearing DIPG patient-derived xenografts were treated with IND of LS-control (empty liposome), LS-CPT-11, or LS-SN-38 by IND for 4 weeks. In vivo responses were measured for tumor growth by serial bioluminescence imaging and animal subject survival. The concentration of SN-38 in the brainstem tumor administered by IND was determined by liquid chromatography-mass spectrometry (LC-MS). Immunohistochemical analyses of the proliferative and apoptotic responses of in vivo tumor cells were performed with Ki-67 and TUNEL staining. LS-SN-38 inhibited DIPG cell growth and colony formation and increased apoptosis, outperforming LS-CPT-11. Rhod-labeled LS-SN-38 showed intracellular fluorescence signals beginning at 30 minutes and peaking at 24 hours following treatment. LC-MS analysis revealed an SN-38 concentration in the brainstem tumor of 0.66 ± 0.25 ng/ml (5.43% ± 0.31% of serum concentration). IND of LS-SN-38 delayed tumor growth and significantly prolonged animal survival compared with IND of LS-control (p < 0.0001) and LS-CPT-11 (p = 0.003). IND of LS-SN-38 increased the number of TUNEL-positive cells and decreased the Ki-67-positive cells in the brainstem tumor. This study demonstrates that IND of LS-SN-38 bypasses the BBB and enables efficient and noninvasive drug delivery to the brainstem tumor, providing a promising therapeutic approach for treating DIPG.